Purification of Anthocyanins Derived from Black Kidney Bean (Phaseolus vulgaris L.) by a Simulated Moving Bed - Liangyu Li; Cheng Luo; Xiqun Zheng (Journal of Chemistry)
Purification of anthocyanins derived from black kidney bean (Phaseolus vulgaris L.) by column chromatography and simulated moving bed (SMB) methods was investigated, and the anthocyanins of black kidney bean were identified. The SMB had advantages over column chromatography in processing efficiency, operation cost, and automation degree in contrast testing. The best SMB conditions resulted in purity and yield of black kidney bean anthocyanins of 24.61 ± 0.21% and 87.85 ± 0.32%, respectively. The half maximal inhibitory concentration (IC50) of 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity and 2,2ʹ-azinobis-(3-ethylbenzthiazoline-6-sulphonate) radical (ABTS+∙) scavenging activity was 0.95 and 2.14 of refined anthocyanins, respectively, indicating strong antioxidant capacity. Three anthocyanins were detected and identified by UPLC-Triple-TOF/MS from black kidney bean skins: delphinidin-3-O-glucoside, petunidin-3-O-glucoside, and malvidin-3-O-glucoside. The experimental results suggested that SMB may help promote industrialization and purification of anthocyanins from colored kidney beans as well as from other plant materials.